PENGARUH MODEL PAIRED STORYTELLING TERHADAP KETERAMPILAN BERCERITA PADA MATA PELAJARAN BAHASA INDONESIA SISWA SEKOLAH DASAR - Rusyda, Siti Hadaina; Sanusi, Ja'far (Elementar : Jurnal Pendidikan Dasar, 2024)
This study aims to determine the influence of the Paired Storytelling model  on storytelling skills in Indonesian subjects of grade IV students of MI Dayatussalam Cileungsi Bogor. This study used quasi-experimental quantitative methods with a population of 62 students consisting of experimental classes and control classes. The data collection techniques used are interviews, observations, and tests. Based  on the results of the Independent Samples Test  table data, the output of the t test results, obtained  the sig value (2-tailed) is 0.010, which means it is smaller than a 0.05 while based on tcalculated t value of 2,644 and ttable  t value of 2,000, tcalculated  t value is  greater than ttable t value.  Thus Ho was rejected and Ha accepted, meaning that there was an influence  of the paired  storytelling model on storytelling skills in subjects Indonesian grade IV students of MI Dayatussalam Cileungsi Bogor.